Hotinja vas and lowland settlement on the western edges of the Pannonian plain in the Early Iron Age. The organization of the settlement and its chronological position - Gerbec, Teja (Arheološki vestnik, 2019)
The article presents the main features of the lowland site of Hotinja vas in the edge of the Drava River plain from the Early Iron Age, the Ha C2–C2/D1 phase. The site was discovered during excavations that accompanied the construction of the Slovenian highway network. Main attention is focused on presenting the discovered dwelling remains, settlement plans, and indicators of its arrangement. Activities are also presented that were recognized on the basis of finds and scientific analyses that were undertaken. The settlement was, as expected, short-lived and was classified chronologically on the basis of study of the finds, statistical analysis of the radiocarbon dates, and the characteristics of the stratigraphic sequence. The significance of the settlement and analogies with other, mostly rural, Iron Age lowland settlements in the Pannonian plain are emphasized.